Management of National Curriculum Integration and Islamic Boarding Schools to Improve the Quality of Graduates at Islamic Boarding Schools in South Tangerang - Maduningtias, Lucia; Ulfiah, Ulfiah; Hanafiah, Hanafiah; Rostini, Dety (International Journal of Science, Technology & Management, 2022)
This research is motivated by the problem of the low quality of education graduates in Indonesia, not yet optimal in the management of education programs, human resources, finance, institutions, and school accountability, learning in Islamic boarding schools is carried out outside school hours allowing for deepening and improvement. an education system that is not a boarding school, because with this system student learning becomes more focused, qualified and adequate, the supervision of educational staff programs has not been carried out optimally, the application of modern management in boarding schools is not optimal so that it has implications for the quality of graduates. The purpose of this study was to determine the activities carried out in planning, organizing, evaluating, the obstacles encountered and solutions to overcome the obstacles. This study uses a qualitative method based on the results of observations, interviews and documentation. This study uses the main theory, namely the management theory of GR Terry. The results of the study show: 1) In planning the integration of the National curriculum and the Islamic Boarding School curriculum to improve the quality of graduates in Islamic boarding schools. through a series of analysis processes, drafting program plans, socialization, financing, and documentation with a bottom-up-top-down or top-down-bottom-up approach, which implies a change in the management paradigm 2) In the implementation of the integration of the National curriculum and Islamic boarding school curriculum to improve the quality of graduates in Islamic boarding school. through the steps of socializing plans, program plans, technical plans, implementation, monitoring, and supervision with a bottom up - top down approach which has implications for the achievement of educational goals and improving the quality of educational outcomes; 3) In the evaluation of learning carried out through self-evaluation, quality internal audits education programs, teacher competency evaluations, management review meetings, and external audits of the quality of education programs; 4) Constraints in the form of differences between the academic year and the budget year, unpreparedness to accept changes in the management paradigm, and lack of knowledge and experience in the management of Islamic Boarding Schools have an impact on the low quality of education and the weak competitiveness of institutions. 5) Solutions, in the form of integrating all school components, compiling all school guidelines, upgrading human resources and all supporting facilities, and building organizational culture and partnerships with implications for the obligation to improve institutional competitiveness, institutional performance, outputs, and outcomes. The conclusion in this study, management of the integration of the National curriculum and Islamic boarding schools to improve the quality of graduates at Islamic boarding schools in South Tangerang City, Banten Province, through the stages of planning, implementation and evaluation is not optimal because there are still weaknesses in management and Human Resources and support from Islamic Boarding Schools.